P56 What is the best method of case finding for chronic viral hepatitis in migrant communities?. (6th September 2011) - Lewis, H; Burke, K; Begum, S; Ushiro-Limb, I; Foster, G
Abstract : Introduction: The prevalence of chronic viral hepatitis in people born in Pakistan living in the UK is 5% (2.7% Hepatitis C Virus (HCV) and 1.8% Hepatitis B Virus (HBV). Studies from the HPA show an increased risk of end stage liver disease from HCV in people from Pakistan living in the UK. Screening migrants from high prevalence regions (>2%) for HBV is cost effective if screening of 35% of a population is achieved. Given that screening for viral hepatitis in migrants will reduce morbidity, mortality and onward transmission of chronic viral hepatitis, the outstanding question is how should this be done? Aim: The aim of this observational study was to evaluate community, and general practice (GP) based approaches to screening migrants for viral hepatitis. Method: We distributed 5000 testing cards in Mosques, following an awareness campaign, encouraging people from Pakistan to attend their GP surgery for viral hepatitis testing. In primary care practices we studied two approaches targeting registered Pakistani/British Pakistani patients: an opportunistic approach, whereby patients attending the practice were offered screening for HBV and HCV, and an 'opt out' approach, where patients were contacted by letter and invited to opt out of screening. Those who did not 'opt out' were telephoned and asked to attend screening clinics. Results: 5000 leaflets were distributed to Mosques but no patients presented to their GP for testing. In the primary care study there were 1163 Pakistani/British Pakistani patients in the 'opportunistic' arm. Of these 17 (1.5%) were screened and all were uninfected. In the 'opt out' arm there were 1134 eligible patients. It was not possible to screen 524 patients (46%) due to inadequate contact details (38%), previous screening (4%) or incorrectly recorded ethnicity (4%). Of those who could be contacted and were eligible for screening, 37% (223/600) have been screened. 75% of those who made a screening appointment were born in Pakistan, and 25% were British Pakistani patients. 1% of those screened were found to be HBsAg positive and 2.4% were HCV antibody positive. Conclusion: Community awareness campaigns and leaflets do not directly lead to testing for viral hepatitis in at risk immigrant groups. A direct screening approach is more effective than an opportunistic screening approach in primary care. Inaccurate GP records reduce the efficiency of screening but GP based testing is easy to implement, popular with patients and effective. First generation migrants are more likely to comply with screening which may improve the cost-effectiveness of this approach.